Teachers’ Job Satisfaction: A Study of Private Schools in Kanakai Municipality - Neupane, Taman (Kanakai Journal, 2022)
The main purpose of the present study was to investigate the determinants that affect private schoolteachers' job satisfaction. This study was conducted at three private schools of Surunga in Kanakai Municipality. The instrument used for data collection was a questionnaire and unstructured interviews of private schools' teachers. The findings of the study revealed that some participant teachers in Surunga perceived teaching as their ideal profession but most of them were engaged in the teaching profession because of the prevalence of private schools in their neighborhoods and lack of employment alternatives. Also, teachers report dissatisfaction about delays in salary payment and most of the teachers are also dissatisfied with available job benefits and security in their chosen profession. The findings suggest that school administrators need to address these important issues, especially regarding equitable payment, on-time salary payment, improved workplace conditions, job security, fair reward system to enhance job satisfaction amongst their employees and increase their physical and mental attachment to the workplace.